Effortless English Learn to Speak English Like a Native - Hoge, C. A (Berkeley [Calif.] Ten Speed Press, 2010)
Effortless English: Learn To Speak English Like A Native A.J. HOGE, THE WORLD'S #1 ENGLISH TEACHER, teaches you his most powerful methods for learning to speak English fluently and confidently. Famous for training corporate and government leaders, A.J. Hoge gives you a step by step program teaching you the system that will help you master English and achieve ultimate success with English. You have studied English for years and yet you still do not speak well. When you speak English, you make grammar mistakes. Your pronunciation is not clear. Worst of all, you feel nervous and shy when you try to speak English. You read English well, but after all these years you still cannot speak well. The good news is, it's not your fault. You have simply used old ineffective methods. Effortless English will teach you a completely new way to learn English faster. Effortless English will..... *Teach you how to overcome nervousness, shyness, and fear when speaking English. *Master spoken English grammar quickly and naturally *Teach you how to improve your English pronunciation and develop an American, British, or Australian accent. *Show you how to achieve a high TOEFL, IELTS, or TOEIC score. *Help you learn vocabulary 4-5 times faster. *Tell you how to feel stronger, calmer, and more powerful when speaking English. *Teach you how to understand native speakers and communicate clearly with them during real conversations. *Help you get better jobs by learning business English. *Teach you how to learn grammar without memorizing grammar rules. "You have studied English many years, yet you still do not speak well. You read English but you feel nervous and frustrated when speaking. It is time for a change. I will teach you to speak English quickly, easily, and automatically using my Effortless English...show more
2
Keywords: English language -- Paragraphs -- Problems, exercises, etc; English language -- Rhetoric -- Problems, exercises, etc; English language -- Sentences -- Problems, exercises, etc